2023
DOI: 10.1002/psp4.12917
|View full text |Cite
|
Sign up to set email alerts
|

Model‐based meta‐analysis of non‐small cell lung cancer with standard of care PD‐1 inhibitors and chemotherapy for early development decision making

Abstract: Single‐arm cohorts/trials are often used in early phase oncology programs to support preliminary clinical activity assessments for investigational products, administered alone or in combination with standard of care (SOC) agents. Benchmarking clinical activity of those combinations against other treatments, including SOC, requires indirect comparisons against external trials, which presents challenges including cross‐study differences in trial populations/other factors. To facilitate such nonrandomized compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…MBMA has been adopted in pharmaceutical research for a variety of disease areas, particularly in nervous system diseases, endocrine/nutritional/metabolic diseases, and neoplasms. For such types of diseases, multiple treatment strategies were developed and tested in many trials, allowing MBMA to estimate the relative effects of different treatments 9,20–24 . For most chronic diseases, such as diabetes and hypertension, which require long‐term management strategies, MBMA is particularly useful in predicting long‐term results based on short‐term data through time event or effect model 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBMA has been adopted in pharmaceutical research for a variety of disease areas, particularly in nervous system diseases, endocrine/nutritional/metabolic diseases, and neoplasms. For such types of diseases, multiple treatment strategies were developed and tested in many trials, allowing MBMA to estimate the relative effects of different treatments 9,20–24 . For most chronic diseases, such as diabetes and hypertension, which require long‐term management strategies, MBMA is particularly useful in predicting long‐term results based on short‐term data through time event or effect model 25 …”
Section: Discussionmentioning
confidence: 99%
“…For such types of diseases, multiple treatment strategies were developed and tested in many trials, allowing MBMA to estimate the relative effects of different treatments. 9,[20][21][22][23][24] For most chronic diseases, such as diabetes and hypertension, which require long-term management strategies, MBMA is particularly useful in predicting long-term results based on short-term data through time event or effect model. 25 Although MBMA has been increasingly used over time, our study suggested that the methodological and reporting quality of MBMA studies remained suboptimal.…”
Section: Articlementioning
confidence: 99%